Cleopatra (1963) [videorecording (DVD)] - Mankiewicz, Joseph L.; Taylor, Elizabeth, 1932-2011; Burton, Richard, 1925-1984; Harrison, Rex; Landau, Martin, 1928-2017; McDowall, Roddy (20th Century Fox Home Entertainment, 2013)
Celebrate the 50th Anniversary of this epic-spectacle; its opulence and sweeping grandeur have never been more glorious. Elizabeth Taylor stars as Cleopatra, the glamorous and cunning queen of Egypt. To secure her hold on power, she seduces the rulers of Rome, only to meet her match in Marc Antony, played by Richard Burton. Their passionate romance could decide the fate of the world's greatest empires.